PROSES PENYERAHAN DAN PERNYATAAN TANAH GARAPAN BERDASARKAN AKTA NOTARIS - Tjhaiyadi, Yuni; Kamarullah, Kamarullah; Sagio, Ibrahim (Faculty Of Law, Universitas Tanjungpura, 2025)
Abtsract Cultivated land on state land is still often found in Indonesia. The handover of cultivated land is still often done while there is a legal vacuum in the absence of regulations regarding the requirements and procedures for the handover of cultivated land or the right to land issued by the Village/Sub-district. This is prone to causing land disputes. Problems, First, how is the process of handing over cultivated land up to land registration at the land office? Second, how is the resolution of land disputes if the handed over cultivated land overlaps between land based on a land statement letter and a certificate of ownership? The method used in this study is normative-empirical legal research. Research results: First, there are no regulations that specifically regulate the requirements and procedures for handing over cultivated land on state land. The handover that has been carried out so far is based on custom and as a completeness of the land registration requirements at the Land Office. Handover using a Notary deed can be accepted in land registration at the land office but must be accompanied by a statement of physical control of the land area. Second, dispute resolution carried out in the event of overlapping land is carried out through mediation at the National Land Agency if a settlement is not reached then it is returned to the disputing parties to be continued to the court. Abstrak ATanah garapan di atas tanah negara masih kerap ditemui di Indonesia. Penyerahan tanah garapan tersebut masih sering dilakukan sedangkan terdapat kekosongan hukum belum adanya peraturan terkait syarat dan tata cara penyerahan tanah garapan maupun alas hak yang diterbitkan oleh Desa/Kelurahan. Hal ini rawan menimbulkan sengketa tanah. Permsalahan, Pertama, bagaimana proses penyerahan tanah garapan sampai dengan pendaftaran tanah di kantor pertanahan? Kedua, bagaimana penyelesaian sengketa tanah apabila tanah garapan yang diserahkan terjadi tumpang tindih antara tanah yang beralaskan surat pernyataan tanah dengan sertifikat hak milik? Metode yang digunakan dalam penelitian ini adalah penelitian hukum normatif-empiris. Hasil penelitian: Pertama, belum ada peraturan yang mengatur syarat dan tata cara penyerahan tanah garapan di atas tanah negara secara spesifik. Penyerahan yang dilakukan selama ini berdasarkan kebiasaan dan sebagai kelengkapan berkas persyaratan pendaftaran tanah di Kantor Pertanahan. Penyerahan menggunakan akta Notaris dapat diterima dalam pendaftaran tanah di kantor pertanahan namun perlu dilengkapi surat pernyataan penguasaan fisik bidang tanah. Kedua, penyelesaian sengketa yang dilakukan apabila terjadi tumpang tindih pertanahan dilakukan melalui mediasi di Badan Pertanahan Nasional apabila tidak tercapai penyelesaian maka dikembalikan kepada para pihak yang bersengketa untuk dilanjutkan ke pengadilan.